Pemecahan Masalah Matematis: Tinjauan pada Mahasiswa Calon Guru Sekolah Dasar - Azhar Syarifuddin; Ahmad Rif'an Najih (STKIP AL HIKMAH SURABAYA, 2025)
This study aims to describe the mathematical problem-solving abilities of prospective elementary school teachers. The study was conducted at STKIP AL Hikmah Surabaya with subjects consisting of 1 high-ability student, 2 medium-ability students and 1 low-ability student. Data collection was carried out by tests and interviews, the results of which were then analyzed based on Polya's problem-solving stages. The results of the tests and interviews showed differences in students' abilities in carrying out the problem-solving stages according to Polya. High-ability students were able to carry out almost all stages well, except for the final evaluation which had not been carried out independently. Medium-ability students understood the questions in general and were able to develop strategies, but often made procedural errors and still relied on feedback to evaluate answers. Meanwhile, low-ability students experienced difficulties from the early stages, from understanding the questions to developing strategies and performing calculations.